SEL204 : Aerobic / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Universiti Teknologi MARA (UiTM), 2018)
Being introduced to the aerobic exercises, the students will identify it as a rapidly developing participation sport, which is undergoing an evolutionary process, because of the new trends in fitness that offers the benefits to produce a vigorous work out.